Comparison of three fish bioaccumulation models for ecological and human risk assessment and validation with field data - Smítková, Hana; Huijbregts, M. A; Hendriks, A. J (SAR and QSAR in environmental research, 2005)
This article compares two bioconcentration Quantitative Structure Activity Relationships (QSARs) for fish applied in human risk assessments with the mechanistic bioaccumulation model OMEGA and field data. It was found that all models are virtually similar up to a Kow of 10(6). For substances with a Kow higher than 10(6), the fish bioconcentration curve in the risk assessment model EUSES decreases parabolically. In contrast, OMEGA bioaccumulation outcomes approximately show a linear increase, based on mechanistic bioconcentration and biomagnification properties of chemicals. The OMEGA-outcomes are close to the fish bioconcentration outcomes of the risk assessment model CalTOX. For very hydrophobic substances, field accumulation data in freshwater and marine fish species are closer to OMEGA- and CalTOX-outcomes compared to EUSES. The results also show that it is important to include biomagnification in fish and lipid content of fish in human exposure models.
Keywords: Models, Biological; biologické modely; hodnocení rizik; sladká voda; zvířata; Fishes; Oceans and Seas; ryby; Animals; lidé; chemické látky znečišťující vodu; kvantitativní vztahy mezi strukturou a aktivitou; Risk Assessment; Fresh Water; Ecology; hydrofobní a hydrofilní interakce; metabolismus lipidů; oceány a moře; Lipid Metabolism; Humans; Hydrophobic and Hydrophilic Interactions; Quantitative Structure-Activity Relationship; Water Pollutants, Chemical; ekologie